Analisis Psikologi Tokoh Utama Dalam Novel ‘’My Idiot Brother’’ Karya Agnes Davonar (Kajian Psikoanalisis Sigmund Freud) - Vanda Zanetha Irijanto; Haerussaleh; Nuril Huda (Journal of Classroom Action Research, 2023)
This research aims to describe the psychology of the main character in the novel "My Idiot Brother" through the study of Sigmund Freud's psychoanalytic segments, including the id, ego, and superego. This qualitative research utilizes a literary psychological research method. The data source for this research is Agnes Davonar's novel "My Idiot Brother," written by Agnes Davonar and published by Inandra in 2011. The data analysis technique used in this research is a descriptive analysis approach with a literary psychological perspective, which involves describing the findings. The analysis results show that the id takes the form of desires and their fulfillment, the ego encompasses behaviors of hatred and an inability to accept reality, and the superego manifests as a sense of conscience towards one's own bad attitudes and regrets.